CLINICAL FEATHERS OF LEIOMYOMA ON THE BACKGROUND OF METABOLIC SYNDROME - Павловська, М.О. (World of Medicine and Biology, 2016)
The research involved 30 patients with leiomyoma associated with metabolic syndrome and 34 control group patients without leiomyoma. Found that in women with uterine leiomyoma associated with metabolic syndrome in the pathogenesis of the disease and age at first period, menopause occurs earlier. Obstetric and gynecological history showed fewer pregnancies and births of some physiological increase in abnormal births, three times more frequently diagnosed infertility. Violation of ovarian-menstrual bleeding occur ovulatory (in 6.7% of cases), excessive bleeding in the perimenopausal period (in 10.0% of cases), the development of amenorrhea and oligomenorrhea. Patients in this group often used hormonal oral contraceptives. Localization of myoma units in the second interstitial age period in 73.1% of cases. Leiomyoma belong to the type I, II and III type equally. Neuro-endocrine status characterized by a probable increase in estradiol levels, decrease – slight decrease of progesterone and DHEA-S. The content of gonadotropin hormones differs little from that of healthy women.
Keywords: uterine leiomyoma; metabolic syndrome; hormonal status